Effect of lithium salt and nano nucleating agent on early hydration of cement based materials. (20th June 2018) - Wang, Jian; Qian, Chunxiang; Qu, Jun; Guo, Jingqiang
Highlights: The lithium salt and nano material are used to accelerate the early hydration. The early strength of cement is studied by studying the early hydration degree. The durability is researched to verify the effect on the properties. Abstract: The purpose of this paper is to study the effects of lithium salt and nano nucleating agent on the properties of cement-based materials, including early hydration, early strength and long-term strength of cement-based materials. The results were as follows: There is a large increase of lithium to cement early hydration, lithium sulfate effect on early hydration of cement than lithium nitrate. Lithium content of 0.3‰ can be very good to promote the early hydration of cement to improve the early strength. nano nucleating agent can significantly improve the early hydration of cement, and the rate of hydration of cement will increase with the increase of the content of nano nucleating agent. However, with the addition of nano nucleating agent, the slurry becomes thick, so adding proper amount of early strength water reducing agent can increase the fluidity of the slurry and improve the performance of the slurry.